Romanian return migration between successful reintegration and the challenge of a new migratory experience - Despina Saghin; Daniel Lucheș; Maria-Magdalena Lupchian; Daniela Jeder (Cogent Social Sciences)
In the last decade, return migration has taken on new dimensions as a consequence of the economic and health contexts, at the European and global levels. The return migration of Romanians is, in most cases, a component part of the initial migration project, the whole migration experience of Romanians being marked by strong ties with the country of origin and family. This study uses data collected through an online survey and a focus group, which targeted return migrants from Suceava County – one of the counties with the highest emigration rate in Romania. The use of these research tools aimed to identify aspects related to the motivation of remigration and the challenges of reintegration of migrants into Romanian society. The results of the survey indicate that return migration is mainly driven by non-economic reasons and corresponds, in most cases, to the initial migration project - to return permanently to the country of origin. The decrease in living standards, unemployment and restrictive local policies expose Romanians returning from abroad to a situation of high vulnerability, making their reintegration difficult, sometimes even impossible. Returning migrants represent a channel for the transmission of knowledge, professional experience, and financial capital; thus, they can be considered a potential source of growth in Romania. The difficulties of reintegration into society contribute to an increase in the degree of economic and psychosocial dissatisfaction of returning migrants, which increases their propensity to re-emigrate and considerably reduces the possibility of permanent settlement in the country of origin.